2019
DOI: 10.1093/mnras/stz1587
|View full text |Cite
|
Sign up to set email alerts
|

Generalised model-independent characterisation of strong gravitational lenses – VI. The origin of the formalism intrinsic degeneracies and their influence on H0

Abstract: We give a physical interpretation of the formalism intrinsic degeneracies of the gravitational lensing formalism that we derived on a mathematical basis in part IV of this series. We find that all degeneracies occur due to the partition of the mass density along the line of sight. Usually, it is partitioned into a background (cosmic) density and a foreground deflecting object. The latter can be further partitioned into a main deflecting object and perturbers. Weak deflecting objects along the line of sight are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 78 publications
(186 reference statements)
0
28
0
Order By: Relevance
“…In principle, there are other ways to describe the deflection of light rays in our universe which are detailed in [27]. For instance, the approach in which the background metric accounts for the entire deflecting mass-density distribution is an equivalent ansatz.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In principle, there are other ways to describe the deflection of light rays in our universe which are detailed in [27]. For instance, the approach in which the background metric accounts for the entire deflecting mass-density distribution is an equivalent ansatz.…”
Section: Methodsmentioning
confidence: 99%
“…As further detailed in [24], this degeneracy can be interpreted as an exact source-position transformation, introduced in [75]. As explained in [27], this degeneracy originates from an a priori arbitrary split of the total deflection potential into a main lens and a perturber. Without additional assumptions or information on the mass-density profile of the axisymmetric lens at r E or on the deflection angle of the perturber, Equations (31) and (32) are under-constrained.…”
Section: The Giant-arc Casementioning
confidence: 97%
See 2 more Smart Citations
“…Making the lens reconstruction independent of specific (parametric) lens models, it was found that these degeneracies that had been treated as global transformations of the entire lens and source plane properties, can be further generalised, such that they locally apply to each system of multiple images individually (Liesenborgs et al 2008a;Liesenborgs & De Rijcke 2012;Wagner 2018). It is clear that these degeneracies cause difficulties in constraining the mass density of a specific lensing object at a certain redshift from such lensing observations, with the integration of mass along the line of sight further confounding the issue (Wagner 2019).…”
Section: Gravitational Lensing Formalismmentioning
confidence: 99%